Sistem Pelayanan Containerisasi Domestik Oleh PT. Salam Pacific Indoenesia Lines Cabang Medan - Sabila, Fadiyah Hani; Melandary, Feny (Majalah Ilmiah Gema Maritim, 2025)
This research aims to describe in detail the Domestic Containerization Service System operated by PT. Salam Pacific Indonesia Lines, Medan Branch. As an archipelagic nation, Indonesia faces significant distribution challenges, and the domestic containerization system has proven effective in reducing logistics costs, accelerating loading and unloading processes, and supporting inter-island trade flows. PT. Salam Pacific Indonesia Lines (SPIL) is one of the largest container shipping service providers in Indonesia, operating since the 1970s. The research methodology employed is Field Research through direct observation at PT. Salam Pacific Indonesia Lines, Medan Branch, supported by Library Research to obtain theoretical data. The domestic containerization service process at the depot includes a series of stages: the delivery of empty and full containers from the depot to the port, the withdrawal of full containers by the consignee and empty containers by the depot, as well as the service of receiving empty containers from the consignee and releasing empty containers to the shipper. This process is supported by the use of information systems such as CIC (Container Inventory Control) to monitor container movement and the MYSPIL BACKEND application for scheduling management. The main obstacles found in the service are delivery delays, damage, and loss of containers, as well as human resource and communication constraints. Furthermore, there are issues regarding data entry errors of container information into the CIC system, which result in manual verification. Efforts to overcome these obstacles include improving process efficiency, routine maintenance, and human resource training. The study concludes that the service system is already good but requires increased accuracy in data input by employees to avoid service delays.